The Development of a 3D Animation to Enhance English Vocabulary Learning for Primary School Students: A Case Study of Zoo Adventure - วรรณยศ กาญจนา; อัศวจุฬามณี ธัญญารัตน์; ธรรมธร สิทธิพร; มลิวัลย์ วินิจชา (การประชุมวิชาการระดับชาติและนานาชาติ เบญจมิตรวิชาการ ครั้งที่ 15, 2025)
The objective of this research was to develop a 3D animation to enhance English vocabulary learning among primary school students, using "Adventure in the Zoo" as a case study. The aim was to create an engaging learning tool that would motivate students and make vocabulary acquisition more enjoyable. The animation was designed as a storytelling-based medium featuring characters and various zoo animals, with accompanying vocabulary words, voiceovers, and basic conversations. The sample group consisted of 15 Grade 4 students from a primary school. The research was conducted in three phases: (1) development of the 3D animation, (2) implementation of the animation in the classroom, and (3) evaluation of students’ satisfaction using a structured questionnaire. The results showed that students improved their English vocabulary knowledge after viewing the animation. Their overall satisfaction with the animation was at a high level, indicating that the 3D animation was effective in promoting learning and could be successfully applied in primary-level English instruction. Specifically, the overall satisfaction score was 4.62, which was considered very good. The satisfaction with the animation development was 4.57 (very good), and the satisfaction with the classroom implementation was 4.67 (very good).